2011
DOI: 10.1002/jcb.23212
|View full text |Cite
|
Sign up to set email alerts
|

Phytoestrogen calycosin-7-O-β-D-glucopyranoside ameliorates advanced glycation end products-induced HUVEC damage

Abstract: Vasculopathy including endothelial cell (EC) apoptosis and inflammation contributes to the high incidence of stroke and myocardial infarction in diabetic patients. The aim of the present study was to investigate the effect of calycosin-7-O-β-D-glucopyranoside (CG), a phytoestrogen, on advanced glycation end products (AGEs)-induced HUVEC damage. We observed that CG can significantly ameliorate AGEs-induced HUVEC oxidative stress and apoptosis. The ratio of SOD/MDA was significantly increased to the normal level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…In agreement with previous study [26,37], we have shown that AGEs induced macrophage migration significantly. However, more importantly, we have shown that pretreatment of anti-HPA antibody, which bind to the C-terminus domain of HPA specially, inhibited the macrophage migration significantly (Figure 2).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In agreement with previous study [26,37], we have shown that AGEs induced macrophage migration significantly. However, more importantly, we have shown that pretreatment of anti-HPA antibody, which bind to the C-terminus domain of HPA specially, inhibited the macrophage migration significantly (Figure 2).…”
Section: Discussionsupporting
confidence: 94%
“…Monocytes transmigrate into the subendothelial space and differentiate into macrophages, which migrate, infiltrate and accumulate in the vascular tissues, involving in diabetic vascular complications. Clinical study has also observed significant increase of AGEs accumulation in diabetic vascular tissues [25], which may induce macrophage migration across an endothelial cell monolayer [26]. …”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids, which are abundant in RA as discussed above [25], have been demonstrated to protect cells from OS damage [39]. It has been reported from us and other research groups that calycosin has protective effect in endothelial cells against hypoxia-induced barrier impairment [40], and calycosin-7-O-β-D-glucosidehas free radicals scavenging activity [41] and it could significantly ameliorate AGEs-induced cell OS and apoptosis in a concentration-dependent manner [32,41].…”
Section: Ra In Directly Inhibited Inflammation Via Ameliorating Oxidamentioning
confidence: 96%
“…Advanced glycation end products (AGEs), which were the key initiator and promoter of T2DM, have been demonstrated to be a class of NF-κB-involved inflammation activators [31]. Recently, we also found and reported that calycosinand calycosin-7β-D-glucoside could significantly decrease inflammatory cytokines secretion, inhibit macrophage inhibition and ameliorate AGEsinduced NF-κB activation in human umbilical vein endothelial cells (HUVECs) [32,33].…”
Section: Ra Directly Inhibited Diabetic Inflammationmentioning
confidence: 99%
“…It is demonstrated that hyperglycemia itself can contribute to OS by forming glycation products that propagate free radicals and enlarge oxidative damage [10]. Moreover, OS itself can induce free radical damage to the DNA and fi nally promote cell apoptosis [11]; furthermore, OS may directly and indirectly up-regulate infl ammatory proteins expression and exaggerate diabetic infl ammation.…”
Section: Introductionmentioning
confidence: 99%